Gregorius Turonensis in njegova Zgodovina Frankov - Hriberšek Vuk, Nina (Keria (Ljubljana), 2003)
Gregorius Turonensis, who was bishop of the city of Tours since 573 A.D., became famous for his ten-volume work called The History of the Franks. As a master of description and narration, he painted a vivid picture of Gaul in the fifth and sixth centuries A.D. This region saw the gradual merging of Gallo-Roman culture with the new ways of life brought in by Germanic peoples during the great migrations, and witnessed the defeat of paganism and the Arian heresy by Christianity, which adhered to the belief in the unity of the Trinity.
Keywords: Franki; Galija; Gregorius iz Toursa; Gregorius Turonensis: Historia Francorum; latinščina; zgodnji srednji vek; zgodovina